External genital injuries in childhood: obey the rules and detect the unseen - Tuncer, Ahmet A.; Embleton, Didem Baskin; User, Nese N.; Cetinkursun, Salih (International Surgery Journal, 2018)
Background: This paper evaluates the patients with external genital organ injuries (EGOI) and the suitability of the Onen’s genital injury scoring (GIS) for the management of such patients. Methods: This is a cross-sectional study. Patients with the complaints of EGOI were retrospectively explored regarding to age, sex, trauma type, hospitalization time, classification of injury type, presence of additional pathologies and treatment methods. After the injury types are classified by using the Onen’s GIS, we investigated the sufficiency of this scoring method for our treatment modalities. Results: A total of 57 patients, 19 females and 38 males, were diagnosed as EGOI. These patients were classified with Grades (G) by using the Onen’s GIS (G1: 42, G2: 7, G3: 5, G4: 2, and G5: 1 patient.). The Grade 5 patient had a colostomy. The external anal sphincters of two patients were repaired to avoid incontinence in the future. The other patients received either medical or non-specific surgical treatments for their injuries. A G3 patient with testicular hematoma had testicular atrophy in the following year. There was no mortality in the present series. Conclusions: The EGOI at childhood ranges from minor derma-abrasion to complete tears of anorectum which requires colostomy. Onen’s GIS ensures better management.